IMPLEMENTATION OF DIGITAL CONTENT ASSISTED LANGUAGE LEARNING (DCALL) IN DEVELOPING FANS TO ENGLISH APPLICATION AS TEACHING MEDIA FOR EFL LEARNERS - Fansury, Andi Hamzah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Digital Content Assisted Language Learning (DCALL) is a new form of learning in the digital era recently. DCALL is a content-based learning digital in the form of writings, images, videos, and authentic material obtained from various sources such as the internet, social media, blogs, email, vlogs, television and so on used to simplify the teaching and learning process. This research aimed to developing the mobile application named Fans to English Application through Digital Content Assisted Language Learning (DCALL). This research used the steps in the combined model of the R & D model and the ADDIE model. The result showed that 1) the application contains material that easier to understand, using audio or video using Indonesian speakers, and interactive exercise so the students can improve speaking skills, and synergizes with the existing curriculum 2) The process of developing Fans to English Application used the android studio application. In the process of making the application, all components, made using Levidio software. 3) The result of beta test was the application can improve students' speaking skills. At this stage the author also shows the practicality of the Fans to English application as digital content assisted language learning where this application can be integrated on various digital platforms.